Manajemen Full Day School di SMA As Safi’iyah Medan - Achmad Zulfikar Siregar (ALACRITY : Journal of Education, 2021)
This study aims to determine Full Day School Management in SMA AS SYAFI’IYAH Medan, Jl. Karya Wisata Ii No.1,Medan Johor, Medan, North Sumatra Province. This research is a qualitative popoulasi study of the Full Day School teacher and management and students of SMA AS SYAFI’IYAH Medan. In an effort to improve student character education in MAN 2, the terrain model includes stages, namely: planning Full Day School learning, implementing Full Day School learning and evaluating Full Day School learning. Learning planning is adapted to the curriculum adopted by SMA AS SYAFI’IYAH Medan, namely the government curriculum, local curriculum and school curriculum and the formulation of syllabus and plan for implementing learning (RPP). The implementation of Full Day School learning consists of habituation activities, exemplary activities, nationalism and patriotism activities and student creativity activities. Evaluation Full Day School learning in general in Medan Model 2 MAN 2 in determining minimal completeness provides an assessment of three domains, namely cognitive, affective and domain psychomotor.